2021
DOI: 10.2106/jbjs.20.01307
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Outpatient Arthroplasty Is Safe Compared with Inpatient Surgery

Abstract: Background: Outpatient joint arthroplasty is a potential modality for increased case throughput and is rising in demand. However, we are aware of no study that has compared outcomes between risk-matched outpatient and inpatient procedures within the last 7 years. The aims of this study were to compare matched patient cohorts who underwent outpatient or inpatient joint arthroplasty in terms of 30-day adverse events and readmission rates. Methods: From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Readmissions comprised 3% of DCAs consistent with recent European studies [ 16 ] as well as with reports published on large overseas patient cohorts [ 4 , 17 , 35 37 ]. There was only one readmission (0.6%) due to a serious complication; a TKA patient with partial pulmonary embolism 7 days after index procedure.…”
Section: Discussionsupporting
confidence: 85%
“…Readmissions comprised 3% of DCAs consistent with recent European studies [ 16 ] as well as with reports published on large overseas patient cohorts [ 4 , 17 , 35 37 ]. There was only one readmission (0.6%) due to a serious complication; a TKA patient with partial pulmonary embolism 7 days after index procedure.…”
Section: Discussionsupporting
confidence: 85%
“…Readmissions comprised 3% of DCAs consistent with recent European studies [16] as well as with reports published on large overseas patient cohorts [4,17,[33][34][35]. There was only one readmission (0.6%) due to a serious complication; a TKA patient with partial pulmonary embolism 7 days after index procedure.…”
Section: Discussionsupporting
confidence: 84%
“…5 6 7 8 9 10 11 12 13 14 15 16 17 More recently, a large database study has demonstrated that inpatient arthroplasty is an independent risk factor for higher rates of adverse events when propensity score matched to outpatient arthroplasty for TKA, THA, and unicompartmental knee arthroplasty. 20 However, these studies did not specifically examine marginalized patients such as those evaluated in this study that have been shown to have decreased satisfaction, worse outcomes, and increased complications after TJA. 26 27 28 29 30 Thus, before transitioning to outpatient TJA at our county hospital, we were unsure whether the challenges unique to this patient population would threaten patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 Furthermore, a recent large database study found that contemporary outpatient TJA is associated with fewer adverse events when matched to inpatient procedures. 20 Compared with inpatient TJA, patients who undergo outpatient TJA may also have higher satisfaction and improved patient-reported outcomes. 10 , 21 …”
mentioning
confidence: 99%